MODEL PEMBELAJARAN PAI BERBASIS IT UNTUK MENINGKATKAN KOMPETENSI PROFESIONALISME GURU PAI DI SD NEGERI 2 DEWANTARA KAB. ACEH UTARA - Daulay, Saripah; Abdullah (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2024)
The process of transferring knowledge to foster students’ comprehension should be done using learning models that are appropriate to current developments of teaching by considering the characteristics of the educational environment and the characteristics of students. Technology is used to assist the learning process in schools. This can be seen by the IT-based learning models that have been used by educators. The purpose of this study is to develop an IT-based Islamic Religious Education learning model, to determine the impact of implementing IT-based Islamic Islamic Education learning models. The subject of the research is at SD Negeri 2 Dewantara Kab. North Aceh. The research method used is development research (research & development) with the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The results of the study are: first, the IT-based Islamic religious education learning model developed in the form of an application called MemBer PAI; second, this IT-based learning model is suitable to be developed for based on the results of validation tests from experts achieving an average score of 4.8 in the very good category; fourth, the use of the PAI MemBer application has an impact on student learning success in achieving an average score above 80 with a completeness percentage of 84% of the total 25 students.